Application of a commercial single-port device for robotic single-incision distal pancreatectomy: initial experience - Peng, Cheng-Ming; Liu, Hsin-Cheng; Hsieh, Ching-Lung; Yang, Yao-Kun; Cheng, Teng-Chieh; Chou, Ruey-Hwang; Liu, Yi-Jui (Surgery today (Tokyo, Japan), 2018)
Purpose Laparoscopic distal pancreatectomy has proven to be feasible and safe. Moreover, robotic surgery provides unique advantages for pancreatic procedures, although single-incision robotic pancreatic surgery is rarely discussed. We applied the single-port modified platform to accomplish robotic distal pancreatectomy in a series of patients. Methods The subjects of this study were ten patients who underwent robotic distal pancreatectomy in our hospital between July 1, 2015 and Dec 31, 2016. All patients were placed supine in the reverse Trendelenburg position with the legs abducted. Surgery was performed via a trans-umbilical 5.0-cm incision, using a modified single-port platform (LAGIPORT ® ) combined with the da Vinci Si Surgical System. The three arms and scope (30-degree up) were inserted through the LAGIPORT ® and positioned in a triangle. Endoscopic ultrasound was used to localize the tumor and plan the resection margin. We recorded the surgical time, operation time, blood loss, postoperative pain score, hospital stay, and complications. Results The surgical time was 236 ± 32 min, the operation time was 172 ± 30 min, and the blood loss was 149 ± 65 ml. All patients underwent robot-assisted distal pancreatectomy without conversion. The average pain score on postoperative day (POD) 3 was 4.5 ± 1. Complications included subsplenic hematoma ( n = 1) and minor pancreatic leakage ( n = 2). There was no surgical mortality. Conclusions Our results demonstrate the safety and efficiency of robotic single-incision distal pancreatectomy via the modified platform (LAGIPORT ® ).